Bacterial Profiling and Dynamic Succession Analysis of Phlebopus portentosus Casing Soil Using MiSeq Sequencing - Yang, Rui-Heng; Bao, Da-Peng; Guo, Ting; Li, Yan; Ji, Guang-Yan; Ji, Kai-Ping; Tan, Qi (Frontiers in Microbiology, 2019)
Phlebopus portentosus (Berk. and Broome) Boedijin is a popular edible mushroom found in China and Thailand. To date, P. portentosus is the only species in the order Boletales that can be successfully cultivated worldwide. The use of a casing layer or casing soil overlaying the substrate is a crucial step in the production of this mushroom. In this study, bacterial profiling and dynamic succession analyses of casing soil during the cultivation of P. portentosus were performed. One hundred and fifty samples were collected, and MiSeq sequencing of the V3-V4 region of the 16S rRNA gene was conducted. After performing a decontamination procedure, only 38 samples were retained, including 6 casing soil-originated samples (OS), 6 casing soil samples (FHCS) and 5 upper substrate samples (FHCU) from the period of complete colonization by mycelia; 6 casing soil samples (PCS) and 5 upper substrate samples (PCU) from the primordium period; and 6 casing soil samples (FCS) and 4 upper substrate samples (FCU) from fruit-body period. The results revealed that bacterial diversity increased sharply from the hyphal to the primordium stage and then decreased in during harvesting. The non-metric multidimensional scaling (NMDS) ordination and analysis of similarities (ANOSIM) analysis suggested that the community composition during different stages was significantly different in casing soil. The most abundant phyla in all of the samples were Proteobacteria, Chloroflexi, Acidobacteria, Actinobacteria, Saccharibacteria and Bacteroidetes. Burkholderia was the most abundant genus in all the samples except the OS samples. The relative abundance of Burkholderia in the FHCS samples (55.79%) decreased to 35.14% in the PCS samples and then increased to 45.60% in the FCS samples. The abundances of Acidobacterium, Rhizobium, Acidisphaera, Bradyrhizobium and Bacillus increased from the FHCS to PCS samples. The linear discriminant analysis (LDA) effect size (LEfSe) suggested that Acidobacterium and Acidisphaera are micromarkers for PCS, whereas Bradyrhizobium, Roseiarcus and Pseudolabrys were associated with fruit body stages. The network analyses resulted in 23 edges, including 4 negative and 19 positive edges. Extensive mutualistic interactions may occur among casing soil bacteria. Furthermore, these bacteria play important roles in mycelial elongation, primordium formations and the production of increased yields.